Metachromasy of a water soluble pthalocyanine dye in the solutions and deposited Langmuir films. (2018) - Shil, A.; Debnath, C.; Hussain, S.A.; Bhattacharjee, D.
Abstract: This communication reports the metachromasy or the changes in shapes and positions of the absorption spectra of an anionic pthalocyanine dye Copper phthalocyanine- 3, 4′, 4″, 4″′- tetrasulfonic acid tetrasoduim salt abbreviated as TS-CuPc, in aqueous solutions and in LB films when electrostatically interacted with a well-known cationic surfactant cetyltrimethylammonium bromide abbreviated as CTAB. Critical Micellar Concentration of CTAB affected largely on the controlling of TS-CuPc molecular aggregates in the CTAB-'TS-CuPc complex LB films. Spectroscopic studies of these LB films showed only monomeric absorption band.